Cool Britannia and multi-ethnic Britain : uncorking the champagne supernova - Arday, Jason (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Cool Britannia and Multi-Ethnic Britain: Uncorking the Champagne Supernova attempts to move away from the melancholia of Cool Britannia and the discourse which often encases the period by repositioning this phenomena through an ethnic minority perspective. In March 1997 the front page of the magazine Vanity Fair announced 'London Swings! Again!' This headline was a direct reference to the swinging London of the 1960s. The English capital which became the era-defining epicentre of the world for its burgeoning rock and pop music scene, with its daring new youth culture, and the boutique fashion houses of Carnaby Street captured most indelibly by the Mods, Rockers and psychedelic hippies of the time. In the 1990's this renewed interest in the swinging 60's seemed to reinvigorate popular culture after a global period in the 1980's which would see the collapse of traditional communism and the ending of Cold War, while ushering in the beginnings of a new technological age spread-headed by Apple, Mircosoft and IBM. The dawn of the 1990's meant that Peace and Love would once reign supreme again; with Britannia being at the forefront of 'cool' again. Godfathers of the Mancunian Rock scene, New Order would declare 'Love had the world in motion' and for a fleeting period, Britain was about to encounter its second coming as the cultural epicentre of the world. While history proffers a period of utopia, inclusion and cultural integration, the narrative considerably alters when exploring this euphoric period through a discriminatory and racialized lens. This book repositions the ethnic minority lived experience during the 1990's from the societal and political margins to the centre. The lexicon explored attempts to provide an altogether different discourse that allows us to reflect on seminal and racially discriminatory episodes during the 1990's that subsequently illuminated the systemic racism sustained by the state. The Cool Britannia Years become a metaphoric reference point for presenting a Britain that was culturally splintered in many ways. This book utilises storytelling and the auto-ethnography as an instrument to unpack the historical amnesia that ensues when unpacking the racialized plights of the time"--
Love spreads : the impact of the cool Britannia years on multi-ethnic Britain -- Don't look back in anger : bringing institutional racism into public focus during the cool Britannia years -- Bitter sweet symphony : reflecting and drawing conclusions on the cool Britannia years on multi-ethnic Britain.
OCLC-licensed vendor bibliographic record.
Keywords: Minorities -- Great Britain -- Social conditions; Great Britain -- Ethnic relations -- History -- 20th century; Great Britain -- Race relations -- History -- 20th century; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General